Cross metathesis of plant oil: A mini review on reaction condition and catalysis - Thangavel, Mythili; S. Y., Chin (IOP Publishing, 2020)
The extensive use of the renewable plant oil-derived polyols could be hindered by its low hydroxyl value owing to the oil saturation level and structural limitations. In recent years, olefin cross-metathesis has turn out to be one of the attractive methods to overcome this constraint by redistributing alkenes fragments and regenerating carbon-carbon double bonds in the plant oil. The product distribution of the cross-metathesis of plant oil is significantly influenced by the types of catalysts and olefin as well as reaction conditions. Accordingly, dissimilar from the extensive reviews on the types of bio-based feedstocks and catalysts for cross metathesis, this article evaluates in specific the operating condition of cross-metathesising the plant oils using different olefins and catalysts, aiming to identify the future research avenues in developing a more technical feasible process to value add the plant oil. It is anticipated that the product yield resulted from the cross-metathesis of another potential feedstocks, the palm oil could be increased within a practical timeframe using 1-propene or 1-octene with a temperature not more than 60 °C and catalyst loading in ppm level.